Effect of elevated ozone, nitrogen availability and mesophyll conductance on the temperature responses of leaf photosynthetic parameters in poplar. (6th February 2020) - Xu, Yansen; Shang, Bo; Feng, Zhaozhong; Tarvainen, Lasse
Abstract: Although ozone (O3 ) concentration and nitrogen (N) availability are well known to affect plant physiology, their impacts on the photosynthetic temperature response are poorly understood. We addressed this knowledge gap by exposing seedlings of hybrid poplar clone '107' ( Populous euramericana cv. '74/76') to elevated O3 (E-O3 ) and N availability variation in a factorial experiment. E-O3 decreased light-saturated net photosynthesis ( A sat ), mesophyll conductance ( g m ) and apparent maximum rate of carboxylation ( V cmax, based on intercellular CO2 concentration) but not actual V cmax (based on chloroplast CO2 concentration) and increased respiration in light ( R d ) at 25 °C. Nitrogen fertilization increased A sat, g m, V cmax and the maximum rate of electron transport ( J max ) and reduced R d at 25 °C and the activation energy of actual V cmax . No E-O3 or E-O3 x N interaction effects on the temperature response parameters were detected, simplifying the inclusion of O3 impacts on photosynthesis in vegetation models. g m peaked at 30 °C, apparent V cmax and J max at 32–33 °C, while the optimum temperatures of actual V cmax and J max exceeded the measured temperature range (15–35 °C). Ignoring g m would, thus, have resulted in mistakenly attributing the decrease in A sat at high temperatures to reduced biochemical capacity rather than to greater diffusion limitation.